Hubungan Status Imunisasi dan Pemberian ASI Eksklusif dengan Kejadian ISPA Pada Bayi 9-12 Bulan Di Wilayah Kerja Puskesmas Kayu Kunyit Kabupaten Bengkulu Selatan - Haryanti, Feri Juli; Rahmarianti, Gusni; Fennyria, Dolis Yesti (Jurnal Kebidanan Manna, 2022)
The purpose of this study was to determine the relationship between immunization status and exclusive breastfeeding with the incidence of acute respiratory infections in infants aged 9-12 months at Kayu Kunyit Health Center Bengkulu Selatan. This research is an analytic study with a cross sectional design. The population of this study were all pregnant women with babies aged 9-12 months in the Kayu Kunyit Health Center working area in January 2022 with a total sample of 57 people. Data analysis was performed by chi-square test. Most had complete infant immunization status (54.4%), with exclusive breastfeeding (56.1%), with infants without Acute Respiratory Infection (59.6%). The results of the statistical test of the immunization status variable and the incidence of Acute Respiratory Infection showed the value of X2 count (10.6) < X2 table (3.481) and the value (0.001) < (0.05) while for the exclusive breastfeeding variable with the incidence of Acute Respiratory Infection, value X2 count (8,6 ) < X2 table (3,481) and value (0,003) < (0,05). There is a significant relationship between immunization status and exclusive breastfeeding with the incidence of acute respiratory infections in infants aged 9-12 months in the Kayu Kunyit Health Center, South Bengkulu Regency.